Rank correlation of resiliency modalities among higher education students in war conditions - Ogorenko Вікторія; Shusterman Тамара; Nikolenko Алла; Kokashynskyi Віктор; Khotimska Анастасія (Psychosomatic Medicine and General Practice, 2024)
Actuality. During the war in Ukraine, the population, including higher education students, faces stress from constant tension caused by concern for their own safety, their relatives and loved ones, a possible negative development of events, training, etc. By developing resilience skills, students will be able to improve their coping with stress. Methods. 174 higher education students were examined, including: 144 students of Dnipro State Medical University (main group) and 30 students of Ukrainian State University of Science and Technology (comparison group). The researchers used a psychodiagnostic method using integrative model of resiliency «BASIC Ph». The results. In the main group of male higher education students, the modalities «Belief», «Socialization» and «Physical» had a direct correlation of moderate strength with all other modalities of coping with stress. A direct correlation of moderate strength between the «Affect» and «Imagination» modalities was also observed. In the comparison group (male gender) «Physical» modality had a direct correlation of moderate strength with the modalities «Socialization», «Affect» and «Imagination». A direct correlation of moderate strength was observed between the «Affect» and «Imagination» modalities. In the main group of female higher education students, a direct weak correlation was observed between «Physical» modality and the modalities «Cognition», «Imagination» and «Affect», as well as between the strategy «Socialization» and «Imagination». A direct correlation of moderate strength was observed between the modalities «Affect», «Imagination» and «Socialization». In the comparison group, a direct correlation of moderate strength was observed between the modality «Belief», «Cognition» and «Physical». Discussion. In both groups of male higher education students, only direct correlations of moderate strength were observed. Overall, male higher education students in the main group demonstrated a greater number of associations between modality scores than did the comparison group. In the groups of female higher education students, correlations of varying strength were observed between the indicators of the modalities. Thus, more correlations were observed in the main group than in the comparison one. Conclusion. When conducting a rank correlation of resiliency modalities among higher education students, a more multifaceted model of coping with stress was revealed in medical students, compared to students of technical specialties. The revealed multifaceted model indicates a more resource-oriented way of coping with stress in medical students, which is the basis for the development and use of resilience, including war conditions. The results of the study should be taken into account when developing psychoeducational and psychocorrective measures and conducting psychological support for students of higher education in the conditions of war and post-war time.